Pemanfaatan Bahan Bio-anorganik untuk Memproduksi Biomassa Hijauan Pakan dan Inokulan Fungi Mikoriza Arbuskula - A D Nusantara; C Kusmana; I Mansur; L K Darusman; Soedarmadi Soedarmadi (Media Peternakan, 2010)
Inoculant production of arbuscular mycorrhizal fungi (AMF) has a vital role in sustaining of higher forage legume production. Currently, it is important to find the alternative materials that can be used as sources of phosphorus due to the need of lower cost, environmentaly friendly, and easily available. Bone meal and rock phosphate are some of the bio-inorganic sources that can be used as a phosphorus source for producing biomass of forage legume and AMF's inoculant production. A glasshouse experiment was conducted to determine the effectiveness of different type of bio-inorganic materials as a fertilizer to increase forage legume biomass and for specific AMF's inoculant production. The experiment was arranged in a factorial randomized block design with two factors, i.e. type of AMF's species (Glomus etunicatum NPI-126 and Acaulospora tuberculata INDO-2) and type of bio-inorganic materials (artifical fertilizer solution as a control, SP36, rock phosphate, and bone meal).  Results showed that G. etunicatum gave better result in terms of host gowth, root colonization and spore production compare to A. tuberculata. Bone meal was better a phosphorus source for AMF's inoculant production instead of artifical fertilizer or other bio-anorganic sources. In conclusion, milled bone meal has a good phosphorus source for AMF's (G. etunicatum) inoculant production